A two-echelon supply chain model with time-varying selling price and demand rate - Maiti, Tarun; Giri, Bibhas Chandra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Prices of hi-tech products usually decline with the passage of time because of rapid technical modernization and universal competitiveness as well as high servicing and maintenance cost after products being sold. In this paper, we develop a two-echelon supply chain model wherein a manufacturer supplies a single high-tech product to a retailer under lot-for-lot policy. The retail price of the product is assumed to be a sum of basic price which is taken as a retail fixed markup (RFM) over the manufacturer’s wholesale price and a variable price which is inversely related to the servicing and maintenance cost. Assuming that the retailer’s demand rate is dependent on the retail price, we develop integrated as well as decentralized models with continuous and discrete time selling prices. For numerical examples, we illustrate the developed models and examine the sensitivity of model-parameters.